KOMUNIKASI INFORMASI DAN EDUKASI (KIE) PENYAKIT LUMPY SKIN DISEASE (LSD) PADA KELOMPOK TERNAK SAPI PERAH - Fidi Nur Aini Eka Puji Dameanti; Viski Fitri Hendrawan; Yudit Oktanella; Sruti Listra Adrenalin; Indah Amalia Amri; Ujiati Kamulyan; Fraya Assifa Mardiyah (LPPM Universitas Al Muslim, 2024)
Lumpy Skin Disease is a smallpox disease on the skin caused by the Lumpy Skin Disease virus from the genus Capripox, family Poxviridae. The LSD virus is double a stranded deoxyribonucleic acid (DNA virus), has a lipid envelope, and replicates in the cytoplasm. This disease can infect cattle and buffalo, and give an economic impact on farmers. Information about LSD in Indonesia has not been published for a long time and has not been published enough, so the Faculty of Veterinary Medicine, Brawijaya University has taken the role of conveying information about LSD through Communication, Information and Education (KIE) media in order to increase awareness of the entry and spread of LSD in areas experiencing LSD outbreaks. The KIE activity was attended by 17 participants from the